Preparation method and application of anti-inflammatory and anti-oxidation nanogel particles based on ammonia-epoxy reaction

Through ammonia-epoxy reaction and click chemical crosslinking technology, the nanogel particle size and the introduction of tannin acid are solved, and the problem of inflexible particle size regulation in the existing technology is achieved, and the efficient drug load of nanogel particles is achieved and Anti-inflammatory and antioxidant function, suitable for the treatment of inflammatory bowel disease.

CN119185334APending Publication Date: 2024-12-27OUJIANG LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411362953.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the existing preparation methods for tannin-based nanogel particles, particle size regulation is inflexible, and organic solvents are often used or physical crosslinking is only dependent on physical crosslinking, which cannot effectively achieve fine control of nanogel particles in drug delivery and targeting.

Method used

The composite behavior of amino compounds and tannin acid is formed through the ammonia-epoxy reaction, combined with ammonia-epoxy click chemical crosslinking, regulate the size of nanogel particles, and introduce hydrophobic drug loading to achieve anti-inflammatory and antioxidant functions.

Benefits of technology

It realizes particle size regulation, biocompatibility and drug load capacity of nanogel particles, provides a green and environmentally friendly preparation method, is suitable for the treatment of inflammatory bowel disease and tissue engineering, and has anti-inflammatory and antioxidant functions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005065384660000011
    Figure HDA0005065384660000011
  • Figure HDA0005065384660000012
    Figure HDA0005065384660000012
  • Figure HDA0005065384660000013
    Figure HDA0005065384660000013
Patent Text Reader

Abstract

The invention belongs to the field of polymer biomedical materials, and particularly relates to a preparation method and application of anti-inflammatory and anti-oxidation nanogel particles based on ammonia-epoxy reaction. The nanogel particles are polymer nanogel particles formed by cross-linking a prepolymer generated by an amine-epoxy reaction of an amino compound and an epoxy compound in water and tannic acid through phase separation mediated by a composite behavior based on hydrogen-bond interaction and an ammonia-epoxy click chemical reaction. The preparation method comprises the following steps: adding an epoxy compound into an amino compound solution, and heating for reaction to obtain an ammonia-epoxy reaction prepolymer solution; adding a tannic acid solution, and shaking and mixing to obtain a prepolymer-tannic acid mixed solution; and adding an epoxy compound, and carrying out heating reaction to obtain the nanogel particles. According to the preparation method, tannic acid is introduced to form nanogel particles through physical crosslinking, and the size of the nanogel particles is regulated and controlled by virtue of an internal three-dimensional network structure of the nanogel particles formed by ammonia-epoxy click chemical reaction crosslinking.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer biomedical materials, and particularly relates to a method for preparing anti-inflammatory and antioxidant nanogel particles based on an ammonia-epoxy reaction and an application thereof. Background Art

[0002] Nanogel particles (NGPs) are usually defined as hydrogel particles with a particle size between 1-1000nm. They are three-dimensional network systems formed by physical or chemical crosslinking of high molecular weight polymers. They play a vital role as delivery systems in biomedical applications. Nanogel particles have the advantages of both hydrogels and nanoparticles: they can swell in water and have a certain degree of adhesion; they can encapsulate drugs in their internal three-dimensional network structure to protect the drugs from damage by the external environment; they have a high drug loading capacity and sustained release; they have a small particle size and thus have a high permeability; they have a huge specific surface area for modification; and they have high biocompatibility and biodegradability. These characteristics make nanogels have broad application prospects as drug delivery carriers. Therefore, the development and utilization of nanogel particles with advanced functionality has become one of the current research hotspots.

[0003] The preparation of nanogel particles can be achieved by two methods: "top-down" (by cutting larger blocks of material until nanoparticles remain) and "bottom-up" (allowing the growth of simple molecules to produce nanoparticles). Among them, for the "bottom-up" preparation method, cross-linked nanogels can be prepared by adopting different strategies. According to the cross-linking method, they can be divided into two categories: physical cross-linking and chemical cross-linking. Among them, physical cross-linking occurs through non-covalent bonds, while chemical cross-linking occurs through covalent bonds. Nanogels based on physical cross-linking can be prepared by self-assembly of polymers in aqueous solution. After mixing polymers in aqueous solution, they will cross-link through hydrogen bonds, van der Waals forces, hydrophobic forces and electrostatic effects to form nanogels. The most commonly used method for chemical cross-linking is free radical polymerization technology, including conventional dispersion polymerization, precipitation polymerization and emulsion polymerization. The main process of conventional free radical polymerization is to dissolve free radical initiators, monomers and stabilizers in a homogeneous or heterogeneous system, and the free radical initiator initiates the polymerization reaction of the monomers to form a three-dimensional network structure of the nanogel.

[0004] Tannic acid (TA), as a natural polyphenol widely found in nature, has attracted much attention due to its excellent biological activities, such as antibacterial, anti-cancer, anti-inflammatory and antioxidant capabilities. However, the existing preparation strategies for tannic acid-based nanogel particles either require the use of organic solvents during the preparation process, or are only based on physical crosslinking between polymers. However, the nanogel particles formed based on physical crosslinking are not flexible enough in regulating the particle size. In short, the existing methods for changing the particle size of gel particles are mainly achieved by changing the type and molecular weight of the polymer. However, at the beginning of the preparation, the molecular weight of the selected polymer is fixed, and the particle size of the particles formed will also be fixed, and it is impossible to achieve flexible regulation of the particle size of the gel particles in situ. The particle size has an important influence on the drug delivery, targeting and clearance of nanogel particles. Summary of the invention

[0005] In view of the defects existing in the prior art, the purpose of the present invention is to provide a method for preparing anti-inflammatory and antioxidant nanogel particles based on ammonia-epoxy reaction and its application in controlled drug release and treatment of inflammatory bowel disease. We achieve the purpose of regulating the size of nanogel particles by changing the overall concentration of the prepolymer-tannic acid mixed solution and the corresponding epoxy compound added. On the one hand, the introduction of tannic acid gives the hydrogel anti-inflammatory and antioxidant properties; at the same time, the internal three-dimensional network structure of the nanogel particles formed by chemical crosslinking of the ammonia-epoxy click chemistry reaction involved in the addition of the epoxy compound can achieve the regulation of the particle size; finally, the internal three-dimensional network structure of the nanogel particles formed after the introduction of tannic acid can load and release hydrophobic drugs with biological functionality in response to reactive oxygen free radicals (ROS), which plays a positive role in the treatment of inflammatory bowel disease.

[0006] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:

[0007] The invention provides a nano gel particle, which is a polymer nano gel particle formed by phase separation mediated by composite behavior based on hydrogen bonding and cross-linking of ammonia-epoxy click chemistry reaction between a prepolymer produced by an amino compound and an epoxy compound in water and tannic acid (TA).

[0008] In the above technical solution, further, the amino compound is a compound with a molecular weight of <10000Da and containing two or more terminal groups as amino groups; the epoxy compound is a compound with a molecular weight of <10000Da and containing two or more terminal groups as epoxy groups.

[0009] In the above technical solution, further, the amino compound is 2-methyl-1,5-diaminopentane (MD); and the epoxy compound is polyethylene glycol diglycidyl ether (PEGDE).

[0010] The present invention also provides a method for preparing the aforementioned nanogel particles, the method comprising:

[0011] (1) dissolving an amino compound in water to obtain an amino compound solution;

[0012] (2) adding an epoxy compound to the amino compound solution of step (1), heating the mixture to react and obtaining an ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution;

[0013] (3) dissolving tannic acid in water to obtain a tannic acid solution; adding the tannic acid solution to the ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution in step (2), and shaking and mixing to obtain a prepolymer-tannic acid mixed solution;

[0014] (4) Adding epoxy compound to the prepolymer-tannic acid mixed solution of step (3), heating and reacting to obtain nanogel particles.

[0015] In the above technical solution, further, in step (1), the concentration of the amino compound solution is 5-20wt%.

[0016] In the above technical solution, further, in step (2), the temperature of the heating reaction is 25-65° C., and the reaction time is 5-100 min.

[0017] In the above technical solution, further, in step (2), the molar ratio of the amino compound to the epoxy compound is 1:3-4:1; and the concentration of the ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution is 5-20wt%.

[0018] In the above technical solution, further, the concentration of the tannic acid solution in step (3) is 0.01-1wt%; the volume ratio of the ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution to the tannic acid solution in step (3) is 1:5 to 5:1.

[0019] In the above technical solution, further, in step (4), the temperature of the heating reaction is 25-65° C., the reaction time is 0.1-10 h, and the mass ratio of the prepolymer-tannic acid mixed solution to the epoxy compound is 1:10 to 10:1.

[0020] The present invention also provides the use of the nanogel particles in oral drug delivery and treatment of inflammatory bowel disease.

[0021] The beneficial effects of the present invention are as follows: the present invention prepares a new tannic acid-based nanogel particle, which has a simple preparation process and a short preparation time, uses water as a solvent, is green and environmentally friendly, and avoids the risk of introducing organic solvents by chemical crosslinking in the preparation of nanogel particles; the introduction of tannic acid forms nanogel particles through physical crosslinking, and the internal three-dimensional network structure of the nanogel particles formed by crosslinking by an ammonia-epoxy click chemical reaction can realize the regulation of the size of the nanogel particles; when the external conditions change, especially when the pH environment changes, the gel is ensured not to disintegrate; the particle size and hydrophobic drug loading capacity of the nanogel particles of the present invention are adjustable; the tannic acid introduced into the nanogel particles can protect tissue cells under oxidative stress, can be used as a functional material in the field of tissue engineering rich in ROS microenvironment, and has biological activity and the ability to load hydrophobic drugs and the ability to release drugs under ROS, and can also be used as a controlled release system to load curcumin (Cur), a hydrophobic drug with anti-inflammatory and antioxidant functions, to reduce the inflammatory response caused by oxidative stress, and finally can also be used as a multifunctional drug carrier to promote the treatment of inflammatory bowel disease. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 SEM images of the freeze-dried nanogel particle samples in Example 1-3;

[0023] Figure 2 Quantification of nanogel particle size in Examples 1-3;

[0024] Figure 3 The hydrodynamic size of the colloidal particles of MDPT3 nanogel particles under different pH conditions in Example 3;

[0025] Figure 4 Infrared spectra of the nanogel particle samples in Examples 1-3;

[0026] Figure 5 Fluorescence image of the nanogel particles in Example 1-3 after being labeled with FITC (fluorescein isothiocyanate);

[0027] Figure 6 Fluorescence image of nanogel particles loaded with nile red in Example 1-3;

[0028] Figure 7 The loading amount of curcumin in the nanogel particles in Examples 1-3 (n=3, the mean±SD);

[0029] Figure 8Evaluation of the therapeutic effects of MDPT3 nanogel particles themselves and MDPT3-Cur loaded with curcumin on inflammatory bowel disease in Example 3: Experimental design and treatment time of DSS-induced IBD model mice and representative images of the colon of mice treated in different ways;

[0030] Fig. 9 Evaluation of the therapeutic effects of MDPT3 nanogel particles themselves and MDPT3-Cur loaded with curcumin on inflammatory bowel disease in Example 3: Disease activity index (DAI) of mice treated in different ways (n=4, **p<0.01);

[0031] Fig.10 Evaluation of the therapeutic effects of MDPT3 nanogel particles themselves and MDPT3-Cur loaded with curcumin on inflammatory bowel disease in Example 3: changes in body weight of mice treated in different ways (n=4, **p<0.01);

[0032] Fig.11 Evaluation of the therapeutic effects of MDPT3 nanogel particles themselves and MDPT3-Cur loaded with curcumin on inflammatory bowel disease in Example 3: colon length of mice treated in different ways (n=4, *p<0.05, **p<0.01);

[0033] Fig.12 Evaluation of the therapeutic effects of MDPT3 nanogel particles themselves and MDPT3-Cur loaded with curcumin on inflammatory bowel disease in Example 3: colon pathology scores of mice treated in different ways (n=4, *p<0.05, **p<0.01, ***p<0.001);

[0034] Fig.13 Evaluation of the therapeutic effects of MDPT3 nanogel particles themselves and MDPT3-Cur loaded with curcumin on inflammatory bowel disease in Example 3: H&E staining images of mouse colon after treatment in different ways;

[0035] Fig.14 Evaluation of the therapeutic effects of MDPT3 nanogel particles themselves and MDPT3-Cur loaded with curcumin on inflammatory bowel disease in Example 3: Immunohistochemical staining images of HO-1 in colon tissues treated in different ways;

[0036] Fig.15 Evaluation of the therapeutic effects of MDPT3 nanogel particles themselves and MDPT3-Cur loaded with curcumin on inflammatory bowel disease in Example 3: Quantification of the immunohistochemical staining area of ​​HO-1 in colon tissues treated in different ways (n=3, *p<0.05);

[0037] Fig.16 Evaluation of the therapeutic effects of MDPT3 nanogel particles themselves and MDPT3-Cur loaded with curcumin on inflammatory bowel disease in Example 3: Biochemical detection of GSH-PX secretion in colon tissues treated in different ways (n=3, *p<0.05, **p<0.01, ***p<0.001);

[0038] Fig.17 Evaluation of the therapeutic effects of MDPT3 nanogel particles themselves and MDPT3-Cur loaded with curcumin on inflammatory bowel disease in Example 3: Biochemical detection of the secretion of T-SOD in colon tissues treated in different ways (n=3, *p<0.05, **p<0.01, ***p<0.001);

[0039] Fig.18 Evaluation of the therapeutic effects of MDPT3 nanogel particles themselves and MDPT3-Cur loaded with curcumin on inflammatory bowel disease in Example 3: Immunohistochemical staining images of M2 (CD206) and M1 (CD86) in colon tissues after treatment in different ways;

[0040] Fig.19 Evaluation of the therapeutic effects of MDPT3 nanogel particles themselves and MDPT3-Cur loaded with curcumin on inflammatory bowel disease in Example 3: Quantification of M2 and M1 cell densities in colon tissues after different treatments (n=3, *p<0.05, **p<0.01). DETAILED DESCRIPTION

[0041] The technical scheme of the present invention is further described below in conjunction with specific embodiments. These embodiments are only used for this description and are not intended to limit the scope of the invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope of protection defined by the present invention. The experimental methods for which specific conditions are not indicated in the embodiments are generally carried out according to conventional conditions and the conditions described in the experimental manual, or according to the conditions recommended by the manufacturer; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.

[0042] Example 1

[0043] 0.29 g of amino compound 2-methyl-1,5-diaminopentane (MD, molecular weight 116.205 Da) was added to 7.47 g of ultrapure water and shaken to dissolve to obtain an amino compound solution; 0.83 g of polyethylene glycol diglycidyl ether (PEGDE) was weighed and added to the amino compound solution obtained previously, shaken to mix, reacted in a water bath at 65° C. for 30 min, then cooled in an ice water bath, shaken to obtain an ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution (prepolymer-MDP, 150 mg / mL); the previously obtained p repolymer-MDP was diluted 400 times to obtain an ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution (prepolymer-MDP1, 0.375 mg / mL); 1.5 mg of tannic acid (TA) was added to 7.5 g of ultrapure water and shaken to dissolve to obtain a tannic acid solution (0.2 mg / mL); 8 mL of the tannic acid solution (0.2 mg / mL) was added to 16 mL of the previously obtained prepolymer-MDP1, and shaken to mix to obtain a prepolymer-tannic acid mixed solution (MDPT1); 24 mL of MDPT1 and 8 mg of polyethylene glycol diglycidyl ether (PEGDE) were mixed, and the mixture was reacted at 65°C in a water bath for 0.5 h to obtain MDPT1 nanogel particles.

[0044] Example 2

[0045] 0.29 g of amino compound 2-methyl-1,5-diaminopentane (MD, molecular weight 116.205 Da) was added to 7.47 g of ultrapure water and shaken to dissolve to obtain an amino compound solution; 0.83 g of polyethylene glycol diglycidyl ether (PEGDE) was weighed and added to the previously obtained amino compound solution, shaken to mix, reacted in a water bath at 65° C. for 30 min, then cooled in an ice water bath and shaken to obtain an ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution (prepolymer-MDP, 150 mg / mL); the previously obtained The prepolymer-MDP was diluted 200 times to obtain an ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution (prepolymer-MDP2, 0.75 mg / mL); 3 mg of tannic acid (TA) was added to 7.5 g of ultrapure water and shaken to dissolve to obtain a tannic acid solution (0.4 mg / mL); 8 mL of the tannic acid solution (0.4 mg / mL) was added to 16 mL of the previously obtained prepolymer-MDP2, shaken to mix, and a prepolymer-tannic acid mixed solution (MDPT2) was obtained; 24 mL of MDPT2 and 16 mg of polyethylene glycol diglycidyl ether (PEGDE) were mixed, and the mixture was reacted at 65° C. in a water bath for 0.5 h to obtain MDPT2 nanogel particles.

[0046] Example 3

[0047] 0.29 g of amino compound 2-methyl-1,5-diaminopentane (MD, molecular weight 116.205 Da) was added to 7.47 g of ultrapure water and shaken to dissolve to obtain an amino compound solution; 0.83 g of polyethylene glycol diglycidyl ether (PEGDE) was weighed and added to the previously obtained amino compound solution, shaken to mix, reacted in a water bath at 65° C. for 30 min, then cooled in an ice water bath, shaken to obtain an ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution (prepolymer-MDP, 150 mg / mL); the previously obtained The prepolymer-MDP was diluted 100 times to obtain an ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution (prepolymer-MDP3, 1.5 mg / mL); 6 mg of tannic acid (TA) was added to 7.5 g of ultrapure water and shaken to dissolve to obtain a tannic acid solution (0.8 mg / mL); 8 mL of the tannic acid solution (0.8 mg / mL) was added to 16 mL of the previously obtained prepolymer-MDP3, and shaken to mix to obtain a prepolymer-tannic acid mixed solution (MDPT3); 24 mL of MDPT3 and 32 mg of polyethylene glycol diglycidyl ether (PEGDE) were mixed, and the mixture was reacted at 65°C in a water bath for 0.5 h to obtain MDPT3 nanogel particles.

[0048] Example 4

[0049] 0.29 g of the amino compound 2-methyl-1,5-diaminopentane (MD, molecular weight 116.205 Da) was added to 7.47 g of ultrapure water, shaken to dissolve, and an amino compound solution was obtained; 0.83 g of polyethylene glycol diglycidyl ether (PEGDE) was weighed, added to the previously obtained amino compound solution, shaken to mix, reacted in a water bath at 65° C. for 30 min, then cooled in an ice water bath, shaken to obtain an ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution (prepolymer-MDP, 150 mg / mL); the previously obtained prepolymer-MDP was diluted 100 times to obtain an ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution (prepolymer-MDP3, 1.5 mg / mL); 8 mL of ultrapure water was added to 16 mL of the previously obtained prepolymer-MDP3, shaken to mix, and a prepolymer-tannic acid mixed solution (MDPT4) was obtained, and 24 mL MDPT4 was mixed with 32 mg of polyethylene glycol diglycidyl ether (PEGDE) and reacted in a water bath at 65° C. for 0.5 h, but no nanogel particles could be obtained.

[0050] Experimental Example 1

[0051] Example 1-4 Nanogel particle morphology and structure:

[0052] In Examples 1-3, we changed the concentration of the prepolymer-tannic acid mixed solution and the mass of the corresponding epoxy compound added in equal proportion. Figure 1 The SEM images of Examples 1-3 are shown in Figures 1-3. It can be clearly seen that as the concentration of the prepolymer-tannic acid mixed solution and the mass of the corresponding added epoxy compound increase in proportion, the size of the nanogel particles in Examples 1-3 increases from 400 nm to 800 nm ( Figure 2 ). In Example 4, the highest concentration of ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution (prepolymer-MDP3, 1.5 mg / mL) was selected, and an ultrapure aqueous solution without tannic acid was added to obtain a prepolymer-tannic acid mixed solution (MDPT4). After adding and mixing with the epoxy compound of medium mass in Example 3, nanogel particles could not be prepared. This shows that the introduction of tannic acid promotes the formation of nanogel particles, and the proportional change of the concentration of the prepolymer-tannic acid mixed solution and the corresponding mass of the added epoxy compound have an important influence on the size of the nanogel particles; the preparation method of the present invention obtains nanogel particles, and the size of the nanogel particles is regulated by adjusting the concentration of the prepolymer-tannic acid mixed solution and the corresponding mass of the added epoxy compound in equal proportion.

[0053] Experimental Example 2

[0054] Example 3 Particle size of nanogel particles at different pH values:

[0055] Figure 3 The hydrodynamic size of the colloid particles of the MDPT3 nanogel particles under different pH conditions in Example 3 shows that when the pH becomes acidic, the nanogel will not disintegrate. The nanogel particles prepared by introducing tannic acid in the present invention achieve physical crosslinking and chemical crosslinking at the same time, and the gel is more stable.

[0056] Experimental Example 3

[0057] Example 1-3 Detection of chemical structure in nanogel particles:

[0058] We analyzed the chemical structure of the nanogel particles prepared in Examples 1-3 by infrared spectroscopy after air drying. Figure 4 It can be seen that tannic acid is indeed introduced into it. At the same time, we used the property of fluorescein isothiocyanate (FITC) that can react with amino groups and emit fluorescence. Through confocal microscopy, we not only demonstrated the existence of amino functional groups in the nanogel particles in Examples 1-3, but also further revealed that their morphology under swelling conditions is similar to that under dry conditions ( Figure 5 ).

[0059] Experimental Example 4

[0060] Example 1-3 Capacity of Nanogel Particles to Load Hydrophobic Drugs:

[0061] We selected the lipophilic fluorescent molecule Nile Red as a drug model, immersed the prepared nanogel particles in Example 1-3 in a 0.1 mg / mL Nile Red (NR) solution (acetone-water mixed solvent) at 65°C for 20 minutes, and loaded at 4°C overnight. Rinse with ultrapure water several times to remove the unloaded Nile Red. Under a confocal microscope, it was observed that the microsphere particle structure area showed a strong red fluorescence signal, indicating that NR was successfully loaded, and the nanogel particles have the potential to load hydrophobic drugs ( Figure 6 ).

[0062] Experimental Example 5

[0063] Example 1-3 Test of the ability of nanogel particles to load curcumin:

[0064] Example 1-3 Nanogel particles have the ability to load hydrophobic drugs. Here, a hydrophobic antioxidant and anti-inflammatory drug Cur was selected and an attempt was made to load it using the three-dimensional network structure in the nanogel particles. Figure 7 It can be seen that the results are consistent with those of the Nile red loading experiment ( Figure 6 ), MDPT3 nanogel particles showed the strongest Cur loading capacity, exceeding 0.26 mg curcumin / g hydrogel loading, while the MDPT1 sample with the smallest nanogel particle size had the smallest loading capacity, only 0.16 mg curcumin / g hydrogel loading. The above results show that the change in nanogel particle size has an important influence on the hydrophobic drug loading capacity. The larger the particle size, the stronger its hydrophobic drug loading capacity, and vice versa.

[0065] Experimental Example 6

[0066] In order to verify whether MDPT nanogel particles have the potential to be used in the treatment of inflammatory bowel disease, we selected the MDPT3 nanogel particles in Example 3 as an example, and evaluated the therapeutic effects of MDPT3 nanogel particles themselves and MDPT3 nanogel particles loaded with curcumin (MDPT3-Cur) on inflammatory bowel disease using a mouse ulcerative colitis model induced by dextran sulphate sodium (DSS). Figure 8-11It can be seen that compared with the untreated DSS group mice, the disease course of the TA group mice, MDPT3 group mice and MDPT3-Cur group mice was relieved to varying degrees from the analysis of DAI, weight change ratio and colon length. Among them, the relief effect of TA was poor, while the relief effect of MDPT3 was better than that of the TA group, and the relief degree of the MDPT3-Cur group mice was the best. In addition, we performed H&E staining on the intestinal tissues treated in different ways, and the results of the histological analysis also showed the same trend, that is, MDPT3-Cur showed the best therapeutic effect on inflammatory bowel disease ( Fig.12 and 13 ).

[0067] Experimental Example 7

[0068] In order to verify whether the MDPT3 nanogel particles themselves and the curcumin-loaded MDPT3 nanogel particles (MDPT3-Cur) in Example 3 have antioxidant properties, we used ROS-related Maker-HO-1 to stain and mark the intestinal tissues treated in different ways. The histological analysis results showed that both MDPT3 nanogel particles and MDPT3-Cur have a scavenging effect on excessive ROS, among which MDPT3-Cur showed a stronger antioxidant capacity ( Fig.14 and 15 ). In addition, we also quantitatively evaluated the levels of glutathione peroxidase (GSH-PX) and total superoxide dismutase (T-SOD) in the intestinal tissues after treatment with different methods. The levels of GSH-PX and T-SOD in the intestinal tissues of the untreated DSS group mice were significantly lower than those in the negative control group (p<0.001). After the action of MDPT3-Cur, the levels of GSH-PX and T-SOD in the intestinal tissues showed a certain degree of increase, indicating that MDPT3-Cur reduced the level of ROS in the intestinal tissues, thereby enhancing the production of antioxidant enzymes such as GSH-PX and T-SOD ( Fig.16 and 17 ). The above results show that this type of MDPT nanogel particles itself has a certain ability to directly consume oxygen free radicals, and can further enhance the consumption of ROS by loading antioxidant drugs such as curcumin.

[0069] Experimental Example 8

[0070] To evaluate whether curcumin-loaded MDPT3 nanogel particles (MDPT3-Cur) have anti-inflammatory function, we used M1 macrophages Maker-CD86 and M2 macrophages Maker-CD206 to stain intestinal tissues treated in different ways. Fig.18 and 19It can be seen that the proportion of M1 macrophages in the intestinal tissue of mice in the untreated DSS group increased significantly (p<0.01). After the action of MDPT3 and MDPT3-Cur, the proportion of M1 macrophages in the intestinal tissue decreased significantly, while the proportion of M2 macrophages increased significantly (p<0.05). The above results show that MDPT3 and MDPT3-Cur can promote the polarization of M1 macrophages to M2 macrophages, accelerate the resolution of inflammation, and show potential in the treatment of inflammatory diseases.

[0071] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A nanogel particle, characterized in that: The nanogel particles are polymer nanogel particles formed by crosslinking of prepolymers produced by amine-epoxy reaction of amino compounds and epoxy compounds in water and tannic acid (TA) through phase separation mediated by composite behavior based on hydrogen bonding and ammonia-epoxy click chemical reaction.

2. The nanogel particles according to claim 1, characterized in that The amino compound is a compound with a molecular weight of less than 10000Da and containing two or more terminal amino groups; the epoxy compound is a compound with a molecular weight of <10000Da compounds containing two or more terminal epoxy groups.

3. The nanogel particles according to claim 2, characterized in that: The amino compound is 2-methyl-1,5-diaminopentane (MD); and the epoxy compound is polyethylene glycol diglycidyl ether (PEGDE).

4. A method for preparing the nanogel particles according to claim 1, characterized in that: The method is: (1) dissolving an amino compound in water to obtain an amino compound solution; (2) adding an epoxy compound to the amino compound solution of step (1), heating the mixture to react and obtaining an ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution; (3) dissolving tannic acid in water to obtain a tannic acid solution; adding the tannic acid solution to the ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution in step (2), and shaking and mixing to obtain a prepolymer-tannic acid mixed solution; (4) Adding epoxy compound to the prepolymer-tannic acid mixed solution of step (3), heating and reacting to obtain nanogel particles.

5. The method for preparing nanogel particles according to claim 4, characterized in that: The concentration of the amino compound solution in step (1) is 5-20 wt %.

6. The method for preparing nanogel particles according to claim 4, characterized in that: The heating reaction temperature in step (2) is 25-65° C., and the reaction time is 5-100 min.

7. The method for preparing nanogel particles according to claim 4, characterized in that: In step (2), the molar ratio of the amino compound to the epoxy compound is 1:3 to 4:1; and the concentration of the ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution is 5-20wt%.

8. The method for preparing nanogel particles according to claim 4, characterized in that: The concentration of the tannic acid solution in step (3) is 0.01-1wt%; the volume ratio of the ammonia-epoxy reaction (polyamino alcohol ether) prepolymer solution to the tannic acid solution in step (3) is 1:5-5:

1.

9. The method for preparing nanogel particles according to claim 4, characterized in that: The temperature of the heating reaction in step (4) is 25-65° C., the reaction time is 0.1-10 h, and the mass ratio of the prepolymer-tannic acid mixed solution to the epoxy compound is 1:10 to 10:

1.

10. Use of the nanogel particles according to claim 1 in oral drug delivery and treatment of inflammatory bowel disease.